PARE0004 Patient reported long term effects of six week progressive resistance training programme for rheumatoid arthritis. (15th June 2017) - Tekkatte, R; Suarez, A; Berntzen, B; Collins, D; Price, E; Williamson, L
Abstract : Background: We introduced six week physiotherapy led progressive resistance training (PRT) programme for Rheumatoid arthritis (RA) patients to improve physical function and prevent the muscle loss (rheumatoid cachexia). Six week data showed improvement in body composition, physical function and fatigue scores 1 . There is little published data about the longer term benefits of short exercise interventions and therefore we wished to study longer term effects on exercise behaviour in our patient group. Methods: We surveyed 79 RA patients who had completed the six weeks PRT programme between 2013 and 2016 using two methods: Anonymous postal questionnaire; Direct telephone questionnaire. Patients were asked the same following questions: 1. Describe the best you feel at present following the exercise programme? Same/ Better/ Worse. 2. Have you continued with progressive resistance exercises? Yes/ No. 3. Do you feel the programme was worthwhile? Yes/No. 4. Did you feel the programme was too long, just right or too short? Results: Postal questionnaire: 45% (36/79) patients returned the postal questionnaire. Time from PRT programme completion to postal questionnaire was: range (mean) 12–36 (26) months. 69% (25/36) still felt better; 25% (9/36) felt the same; 3% (1/36) worse since the programme. 91% (33/36) felt the programme was worthwhile. 75% (27/36) continued PRT exercises. 81% (22/27) of these still felt better, compared with 33% (3/9) who have not continued PRT (p=0.006). The duration of the programme was just right for 69% (25/36) and too short for 30% (11/36). Telephone questionnaire: 54% (43/79) patients were contactable by telephone. Time from PRT programme completion to telephone questionnaire was: range (mean) 14–38 (26) months. 58% (25/43) still felt better; 18% (8/43) felt the same; 23% (10/43) worse since the programme. 95% (41/43) felt the programme was worthwhile. 51% (22/43) continued PRT exercises. 77% (17/22) still felt better, compared with 38% (8/21) who have not continued PRT. (p=0.009). 49% (21/43) had not continued PRT exercises, of whom 43% feel worse at present. The duration of the programme was just right for 47% (20/43) and too short for 53% (23/43). Conclusions: Over 90% of patients who responded found the six week PRT programme worthwhile. More than half (51–75%) of the patients continued a PRT exercise programme. Patients who continued exercises felt better compared with those who did not continue exercises. References: Berntzen et al A Six-Week Progressive Resistance Training Class Improves Function and Fatigue in RA Patients: Annals of the Rheumatic Diseases 75 (S2):254 2016. Disclosure of Interest: None declared